1998
DOI: 10.1038/sj.bjp.0702243
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of wortmannin on the release of substance P and amino acids from the isolated spinal cord of the neonatal rat

Abstract: 1 E ects of wortmannin, an inhibitor of myosin light chain kinase, on the release of substance P and amino acids, GABA and glutamate, were investigated in the isolated spinal cord preparation of the neonatal rat. 2 Wortmannin at 0.5 ± 10 mM depressed the release of substance P evoked by high-K + (90 mM) medium from the spinal cord (IC 50 =1.1 mM). Wortmannin also depressed the high-K + (70 mM)-evoked release of substance P from cultured dorsal root ganglion neurons of neonatal rats. In contrast, the high-K + (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated the importance of various intracellular signaling factors, including MAP kinases, in the regulation of SP release from neurons (Suzuki et al. 1998; Tang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of various intracellular signaling factors, including MAP kinases, in the regulation of SP release from neurons (Suzuki et al. 1998; Tang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding their identity, binding of the transmitter-containing SVs and/or LDCVs to PtdIns(4,5)P 2 would target the release of their transmitters to specific microdomains in the plasma membrane. A role of other phosphorylated phosphoinositide recruitment sites in differential regulation of LDCV and SV exocytosis was proposed by experiments in rat spinal cord [120]. Pharmacological blockade of phosphatidylinositol 3-kinase selectively reduced release of substance-P peptide without affecting the release of glutamate and GABA.…”
Section: Inositol Phosphate Signaling and Differential Neurotransmittmentioning
confidence: 98%
“…A precise role for PI 3-kinase in nerve terminal function has not been established (12)(13)(14), despite that its lipid products play numerous roles the actin cytoskeleton and in vesicle trafficking (15, 16). Synapsin I also connects vesicle traffic with the actin cytoskeleton and the synapsin-p85 in vitro interaction suggests that PI 3-kinase activity might play a role in SV recycling if it occurred in nerve terminals.…”
mentioning
confidence: 99%